2015
DOI: 10.3168/jds.2014-8794
|View full text |Cite
|
Sign up to set email alerts
|

Potential of milk fatty acid composition to predict diet composition and authenticate feeding systems and altitude origin of European bulk milk

Abstract: The aims of this work were to elucidate the potential of using milk fatty acid (FA) concentration to predict cow diet composition and altitude of bulk milk collected in 10 different European countries and to authenticate cow-feeding systems and altitude of the production area using a data set of 1,248 bulk cow milk samples and associated farm records. The predictions based on FA for cow diet composition were excellent for the proportions of fresh herbage [coefficient of determination (R2)=0.81], good for hay, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
42
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 41 publications
13
42
0
Order By: Relevance
“…Similarly, also the SFA content of pasture-derived cheese was 74.87g/100 g FA lower than that of the control cheese. This is in coherence with similar finding in Europe (Coppa et al, 2015;Bovolenta et al, 2014).…”
Section: Resultssupporting
confidence: 81%
“…Similarly, also the SFA content of pasture-derived cheese was 74.87g/100 g FA lower than that of the control cheese. This is in coherence with similar finding in Europe (Coppa et al, 2015;Bovolenta et al, 2014).…”
Section: Resultssupporting
confidence: 81%
“…However, the aforementioned studies followed the evolution of the FA composition of milk collected from individual animals throughout the entire lactation period in controlled condition and with a constant diet . On the other hand, the effect of animal related factors, such as breed and lactation stage, is known to have a negligible effect on the FA composition of milk in dairy cows on farms, compared to animal diet . The results of the present study have shown a greater effect on milk FA of the farming system, with a limited effect of the lactation stage, which is indicated by the higher ANOVA Fisher's F coefficients for the farm effect than for DIM.…”
Section: Discussionmentioning
confidence: 54%
“…Milk samples were analyzed for FA composition by gas chromatography (GC), as described by Coppa et al . The method was adapted to donkey milk because of the lower lipid content and its larger variation in donkey milk than in cow milk.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, previous studies have associated the effect of grazing on enrichment of ALA in ruminant tissues with botanical and thus biochemical diversity, in particular with a diversity of plants with elevated contents of secondary compounds (Leiber et al, 2005;Ferlay et al, 2006;Cabiddu et al, 2010;Willems et al, 2014), which can influence ruminal biohydrogenation. Generally, in the present as well as in other meta-analyses (Coppa et al, 2013(Coppa et al, , 2015, grazing appears as a feeding strategy that has a particular strong influence on the milk FA profiles.…”
Section: Effects Of Feeding Regimen On Milk C18 Fa Proportionsmentioning
confidence: 92%